Application of atom probe tomography to fundamental issues of steel materials. (3rd September 2018) - Takahashi, Jun; Kawakami, Kazuto; Kobayashi, Yukiko
Abstract : Although steel research has a very long history, there are still various questions and uncertainties on the fundamental issues of steel materials. Our aim is to clarify the issues by atomic‐scale characterization using atom probe tomography (APT). This paper introduced our developed techniques in application of APT into steel materials. The first one is the specimen tip preparation technique from the site‐specific regions of interest in steel, which significantly expanded the application field of steel analysis. The second one is the observation technique of trapped hydrogen in steel using our developed "deuterium charge cell, " which accomplished direct observation of the hydrogen trapping site in alloy carbide precipitation strengthened steels. Such atomic‐scale analyses bring many new findings in steel materials science.